Temporary Reversal of Blood Flow During Transcarotid Artery Revascularization Does Not Change Brain Electrical Activity in Lead-In Cases of the ROADSTER 1 Multicenter Trial. (December 2018) - King, Alexander H.; Motaganahalli, Raghu L.; Siddiqui, Adnan; DeRubertis, Brian; Moore, Wesley S.; DiMuzio, Paul; Eccher, Matthew A.; Kashyap, Vikram S.
Purpose: To evaluate any intraoperative electroencephalographic (EEG) changes accompanying reversed flow with the ENROUTE Transcarotid Neuroprotection System during transcarotid artery revascularization (TCAR).Methods: A post hoc analysis was performed of the first 81 consecutive lead-in patients (mean age 72.8±8 years; 61 men) enrolled in the ROADSTER 1 trial at 5 participating institutions. All patients had high-grade carotid artery stenosis [53 (59.3%) left sided; 12 (14.8%) contralateral occlusions] and high-risk criteria for carotid endarterectomy. A third had symptoms of either stroke (13, 16.0%) or transient ischemic attack (14, 17.3%). This subset of early patients underwent EEG monitoring to detect any cerebral changes during reversed flow as an added safety measure mandated by the ROADSTER 1 trial protocol.Results: Mean flow reversal time was 12.9±8.2 minutes. The goal mean arterial pressure during reversed flow was 100 mm Hg, but 7 (8.6%) patients suffered hypotension. One (1.2%) patient had slight EEG changes secondary to blood pressure fluctuation; these resolved with blood pressure elevation. No other EEG changes were noted. One (1.2%) patient had a postoperative stroke and another (1.2%) had postoperative myocardial infarction (MI), leading to 2.5% 30-day stroke/death/MI rate.Conclusion: Temporary reversal of blood flow during TCAR is a safe maneuver and does not cause cerebral ischemia in the vast majority of patients, including those with contralateral carotid occlusion. Carotid stenting performed with reversed blood flow mitigates cerebral embolization and periprocedural stroke without concern for brain ischemia.